Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1103/physrevb.84.245315
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quantum Monte Carlo with time-dependent and static density-functional theory calculations of diamondoid excitation energies and Stokes shifts

Abstract: We compute the absorption and emission energies and hence Stokes shifts of small diamondoids as a function of size using different theoretical approaches, including density-functional theory (DFT) and quantum Monte Carlo (QMC) calculations. The absorption spectra of these molecules are also investigated by time-dependent DFT and compared with experiment. We analyze the structural distortion and formation of a self-trapped exciton in the excited state, and we study the effects of these on the Stokes shift as a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…Our calculations yield substantial redshifts of 650, 550 and 490 meV for adamantane, diamantane and triamantane, respectively, reflecting significant structural relaxations upon photoexcitation. with the calculations of Marsusi et al 21 (Supplementary Note 1) reduces the discrepancy between experimental and Quantum Monte Carlo-calculated optical gaps from 0.8 to 0.3 eV. This difference is within the error bar estimated by Marsusi et al 21 , and is of the order of the difference between DMC data and GW calculations of the ionization potentials 32 .…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Our calculations yield substantial redshifts of 650, 550 and 490 meV for adamantane, diamantane and triamantane, respectively, reflecting significant structural relaxations upon photoexcitation. with the calculations of Marsusi et al 21 (Supplementary Note 1) reduces the discrepancy between experimental and Quantum Monte Carlo-calculated optical gaps from 0.8 to 0.3 eV. This difference is within the error bar estimated by Marsusi et al 21 , and is of the order of the difference between DMC data and GW calculations of the ionization potentials 32 .…”
Section: Resultssupporting
confidence: 61%
“…with the calculations of Marsusi et al 21 (Supplementary Note 1) reduces the discrepancy between experimental and Quantum Monte Carlo-calculated optical gaps from 0.8 to 0.3 eV. This difference is within the error bar estimated by Marsusi et al 21 , and is of the order of the difference between DMC data and GW calculations of the ionization potentials 32 . This result identifies the change in quantum nuclear energy upon photoexcitation as the missing physics in previous attempts at explaining the optical properties of diamondoids 6,21,33 .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15] In particular, the observation of photoluminescence (PL) in reduced-dimensional semiconductor systems, which otherwise exhibit an indirect band gap, like Si and C (diamond), opens possibilities to tailor their optical properties and to interface with already existing technologies. [2][3][4] However, despite numerous studies, [2][3][4]16,17 the fundamental photophysical processes in such systems still are not fully understood. In order to gain a deeper insight into these processes, it is desirable to perform experiments under idealized conditions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…high excitation energies with respect to the optical gap [E gap ]) caused the spectrum to be completely congested, thus lacking any vibrational fine structure, making it difficult to compare with calculations. 16 The optical properties of gas phase polymantanes have so far only been investigated with absorption spectroscopy. 2 This study showed that the basic shape (1-, 2-, & 3-dimensional) of the diamondoids is reflected in the overall shape of its absorption spectrum.…”
Section: Introductionmentioning
confidence: 99%